Induction of luteolysis in mares utilizing a micro-dose of prostaglandin F-2 alpha in the sacral lumbar space - Alvarenga, Marco Antonio [UNESP]; Ferreira, JPC; Meira, Cezinande de [UNESP]; Luna, Stelio Pacca Loureiro [UNESP]; Burns, P. J. (Equine Nutrition & Physiology Society, 1997)
An experiment was conducted to examine the luteolytic effectiveness of using low or micro doses of PGF(2 alpha) when administered at the (BAI HUI) acupuncture point, which is frequently used to treat ovarian disturbances in Veterinary Acupuncture. The results indicate that PGF(2 alpha) given at a very low micro dose of 0.5mg (one tenth the conventional recommended dose) when administered at the BAI HUI acupuncture point located at the sacral lumbar space is equally effective at inducing luteolysis in mid-luteal phase mares as conventional PGF(2 alpha) i.m. treatment using a tenfold higher dose. Therefore, based on the results of the present study we suggest that the BAI HUI sacral lumbar route somehow provides an extremely efficient pathway for the drug to the ovarian level.
Keywords: mare; luteolysis; PGF(2 alpha); BAI HUI acupuncture point; sacral lumbar space